Proximate Composition and Sensory Characteristics of Traditional and Oven-Drying Smoked Tilapia Fillets Enriched With Olive Oil - Ikasari, Diah; Suryanti, Suryanti; Suryaningrum, Theresia Dwi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
The study aimed to investigate the chemical and organoleptic characteristics of smoked tilapia fish fillets which were produced using different drying process and enriched with olive oil. Smoked fish were made using the following method: the fish were fasted overnight, shocked with cold water (4-5 oC) and then slaughtered and filleted. The fillets were soaked for 30 minutes in a brine solution containing spices and 5% (v/v) of liquid smoke. 5% (v/v) of olive oil was added into the solution and compared with control without olive oil addition. After 30 minutes, fish were cleaned from the spices using water and smoked at a temperature of 80 oC for 4-5 hours. The drying process was conducted in two different methods, i.e using oven-drying and traditional smoking. The smoked tilapia products were analyzed for proximate composition and sensory profiles. The result showed that addition of olive oil and methods of drying affected the proximate composition as well as sensory characteristics of the tilapia fillets. The fillets with addition of 5% olive oil and processed with oven-drying were considered as the best treatment due to low moisture content but high ash, fat and protein contents with 45.6±0.4%; 6.8±0.1%; 7.9±0.1% and 82±1.6%,  respectively. Based on panelist evaluation, the fillets with 5% olive oil and processed with oven-drying also had high performances in appearance and texture.